Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
20x + 15y + 12z = 60 ⇒ 20x + 15y + 12z = 60
10x + 30y + 12z = 60 ⇒ 20x + 60y + 24z = 120
-45y - 12z = -60
-45y + 45y - 12z = -60 + 45y
-12z = -60 + 45y
-12 -12
z = 5 - 45/12y
20x + 15y + 12(5 - 45/12y) = 60
20x + 15y + 12(5) - 12(45/12y) = 60
20x + 15y + 60 - 45y = 60
20x + 15y - 45y + 60 = 60
20x - 30y + 60 = 60
-60 -60
20x - 30y = 0
20x - 20x - 30y = 0 - 20x
-30y = -20x
-30 -30
y = 2x/3
20x + 15(2x/3) + 12(5 - 45/12y) = 60
20x + 10x + 60 - 45y = 60
30x - 45y + 60 = 60
-60 -60
30x - 45y = 0
30x - 45y + 45y = 0 + 45y
30x = 45y
30 30
x = 3/2y
20(3/2y) + 15(2x/3) + 12(5 - 45/12y) = 60
30y + 10x + 60 - 45y = 60
10x + 30y - 45y + 60 = 60
10x - 15y + 60 = 60
-60 -60
10x - 15y = 0
10(3/2y) + 30(2x/3) + 12(5 - 45/12y) = 60
15y + 20x + 60 - 45y = 60
20x + 15y - 45y + 60 = 60
20x - 30y + 60 = 60
-60 -60
20x - 30y = 0
10x - 15y = 0 ⇒ 20x - 30y = 0
20x - 30y = 0 ⇒ 20x - 30y = 0
-60y = 0
-60 -60
y = 0
10x - 15(0) = 0
10x - 0 = 0
+0 +0
10x = 0
10 10
x = 0
20x + 15y + 12z = 60
20(0) + 15(0) + 12z = 60
0 + 0 + 12z = 60
0 + 12z = 60
12z = 60
12 12
z = 5
(x, y, z) = (0, 0, 5)
10x + 30y + 12z = 60 ⇒ 20x + 60y + 24z = 120
-45y - 12z = -60
-45y + 45y - 12z = -60 + 45y
-12z = -60 + 45y
-12 -12
z = 5 - 45/12y
20x + 15y + 12(5 - 45/12y) = 60
20x + 15y + 12(5) - 12(45/12y) = 60
20x + 15y + 60 - 45y = 60
20x + 15y - 45y + 60 = 60
20x - 30y + 60 = 60
-60 -60
20x - 30y = 0
20x - 20x - 30y = 0 - 20x
-30y = -20x
-30 -30
y = 2x/3
20x + 15(2x/3) + 12(5 - 45/12y) = 60
20x + 10x + 60 - 45y = 60
30x - 45y + 60 = 60
-60 -60
30x - 45y = 0
30x - 45y + 45y = 0 + 45y
30x = 45y
30 30
x = 3/2y
20(3/2y) + 15(2x/3) + 12(5 - 45/12y) = 60
30y + 10x + 60 - 45y = 60
10x + 30y - 45y + 60 = 60
10x - 15y + 60 = 60
-60 -60
10x - 15y = 0
10(3/2y) + 30(2x/3) + 12(5 - 45/12y) = 60
15y + 20x + 60 - 45y = 60
20x + 15y - 45y + 60 = 60
20x - 30y + 60 = 60
-60 -60
20x - 30y = 0
10x - 15y = 0 ⇒ 20x - 30y = 0
20x - 30y = 0 ⇒ 20x - 30y = 0
-60y = 0
-60 -60
y = 0
10x - 15(0) = 0
10x - 0 = 0
+0 +0
10x = 0
10 10
x = 0
20x + 15y + 12z = 60
20(0) + 15(0) + 12z = 60
0 + 0 + 12z = 60
0 + 12z = 60
12z = 60
12 12
z = 5
(x, y, z) = (0, 0, 5)
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.